The Urgency of Recognizing the 'Opt-Out Right' to Protect Consumer Personal Data in P2P Lending Fintech - Nadia Carolina Weley; Shenti Agustini; David Tan; Tony Wibowo; Tony Tan (Greenation International Journal of Law and Social Sciences, 2026)
Financial Technology (FinTech) has significantly advanced financial services in the digital era, with Peer-to-Peer (P2P) lending platforms emerging as a major example. While these platforms provide financial assistance, many operate under the principle of "forced consent," where users are required to agree to unnecessary data processing, such as for marketing or data analysis, as a condition for accessing core services. This practice violates the "lawful consent" principle outlined in the 1945 Constitution of the Republic of Indonesia and is implicitly prohibited under Law Number 27 of 2022 on Personal Data Protection and regulations by the Financial Services Authority. This study proposes a concrete solution by advocating for the adoption of the "Right to Opt-Out," a principle effectively implemented by the European Union through the General Data Protection Regulation (GDPR). The Right to Opt-Out allows individuals to refuse or limit the use of their personal data without losing access to essential services. Using a normative legal research method with a statutory approach, the study recommends incorporating the Right to Opt-Out into Indonesia's data protection framework, enhancing legal certainty and empowering consumers to control their personal data in P2P lending services.